A Synthesis Inversion to Constrain Global Emissions of Two Very Short Lived Chlorocarbons: Dichloromethane, and Perchloroethylene. Issue 12 (18th June 2020) - Claxton, Tom; Hossaini, Ryan; Wilson, Chris; Montzka, Stephen A.; Chipperfield, Martyn P.; Wild, Oliver; Bednarz, Ewa M.; Carpenter, Lucy J.; Andrews, Stephen J.; Hackenberg, Sina C.; Mühle, Jens; Oram, David; et al.
Abstract: Dichloromethane (CH2 Cl2 ) and perchloroethylene (C2 Cl4 ) are chlorinated very short lived substances (Cl‐VSLS) with anthropogenic sources. Recent studies highlight the increasing influence of such compounds, particularly CH2 Cl2, on the stratospheric chlorine budget and therefore on ozone depletion. Here, a multiyear global‐scale synthesis inversion was performed to optimize CH2 Cl2 (2006–2017) and C2 Cl4 (2007–2017) emissions. The approach combines long‐term surface observations from global monitoring networks, output from a three‐dimensional chemical transport model (TOMCAT), and novel bottom‐up information on prior industry emissions. Our posterior results show an increase in global CH2 Cl2 emissions from 637 ± 36 Gg yr −1 in 2006 to 1, 171 ± 45 Gg yr −1 in 2017, with Asian emissions accounting for 68% and 89% of these totals, respectively. In absolute terms, Asian CH2 Cl2 emissions increased annually by 51 Gg yr −1 over the study period, while European and North American emissions declined, indicating a continental‐scale shift in emission distribution since the mid‐2000s. For C2 Cl4, we estimate a decrease in global emissions from 141 ± 14 Gg yr −1 in 2007 to 106 ± 12 Gg yr −1 in 2017. The time‐varying posterior emissions offer significant improvements over the prior. Utilizing the posterior emissions leads to modeled tropospheric CH2 Cl2 and C2 Cl4 abundances and trends in good agreement to those observed (including independent observations to the inversion). A shorter C2 Cl4 lifetime, from including an uncertain Cl sink, leads to larger global C2 Cl4 emissions by a factor of ~1.5, which in some places improves model‐measurement agreement. The sensitivity of our findings to assumptions in the inversion procedure, including CH2 Cl2 oceanic emissions, is discussed. Plain Language Summary: The 1987 Montreal Protocol banned production for dispersive uses of major ozone‐depleting gases, such as chlorofluorocarbons, due to their role in depletion of the stratospheric ozone layer. In consequence, the ozone layer is expected to recover in coming decades, as stratospheric chlorine from banned substances slowly declines. However, chlorinated very short lived substances (Cl‐VSLS), not controlled by the Montreal Protocol, represent a small, but growing, source of atmospheric chlorine that could potentially slow ozone recovery. It is thus important that the magnitude of emissions of these compounds, their spatial distribution, and changes with time are quantified. Here, we combined observations of Cl‐VSLS, prior estimates of their emissions, and a chemical transport model to produce an optimized set of emission estimates on a region‐by‐region basis between 2006 and 2017. We show that industrial emissions of dichloromethane, the most abundant Cl‐VSLS, increased by ~84% within this period, predominately due to an increase in Asian emissions, while European and North American emissions decreased. Over 2007–2017, emissions of perchloroethylene, a less abundant Cl‐VSLS, decreased, particularly in Europe and North America. We show that our new emission estimates lead to better agreement with observational data compared to previous estimates. Key Points: Global CH2 Cl2 emissions increased by ~85% between 2006 and 2017, mostly due to increasing emissions from Asia Global C2 Cl4 emissions decreased in the same period by ~25%, mainly due to reduced emissions from Europe and North America Posterior CH2 Cl2 and C2 Cl4 emissions provide good agreement with surface and aircraft observational data